Rekonstruksi Karya Pneumatologis dalam Bingkai Aktivisme Sosial Pentakostal di Indonesia - Kosma Manurung (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Abstract. This study is an attempt to build a theological view on the social activism of Pentecostals in Indonesia. Pentecostals in Indonesia are actually very familiar with social activities in the community. Otherwise, there would not be many Pentecostal Churches in various regions, which indicates the acceptance of the local community. However, such social activities are often understood separately from the understanding of the work of the Holy Spirit, or often understood to achieve the goal of proselytization. This study is conducted by re-reading the narratives of Joseph and Daniel in the Old Testament from the perspective of the Pneumatic work. The results of this study showed that the Spirit of God is the power that moves believers to work for the transformation of society.Abstrak. Kajian ini adalah sebagai upaya untuk membangun suatu pandangan teologis atas aktivisme sosial kaum Pentakostal di Indonesia. Kaum Pentakostal di Indonesia sebenarnya sudah sangat akrab dengan aktivitas sosial di tengah masyarakat. Jika tidak demikian, tidak mungkin banyak berdiri Gereja Pentakostal di berbagai daerah, yang mengindikasikan penerimaan masyarakat setempat. Namun, aktivitas sosial tersebut sering dipahami terpisah dengan pemahaman akan karya Roh Kudus, atau sering dipahami sebagai sarana mencapai tujuan proselitisasi. Kajian ini dikerjakan dengan membaca ulang narasi Yusuf dan Daniel di Perjanjian Lama dalam perspektif karya Pneumatologis. Hasil kajian ini menunjukkan bahwa Roh Tuhan adalah daya yang menggerakkan orang yang beriman untuk berkarya bagi transformasi masyarakat.